Foreign Trade of the Republic of Kazakhstan with the Member States of the Eurasian Economic Union: State and Perspectives - Zhanakova, Nazigul Nurlanovna (International Journal of Economics and Financial Issues, 2016)
The rapid development of foreign trade can stimulate the development of production capacity; thereby contribute to the growth of GDP. However, if the state’s economy is growing one-sided, then the excessive dependence of the economy on the situation in the world primary commodity markets poses serious risks for sustainable economic development. Therefore, in the formation of the Common Economic Space, strengthening the strategic partnership and deepening trade relations between the member countries of the EEU is a regular consequence of the development of allied relations. Every year, the trade turnover between the countries is growing, and work is being actively carried out to harmonize the legislation and simplify the mechanisms of cooperation between the residents of the partner countries. Keywords: Foreign trade, Eurasian Economic Union, Republic of Kazakhstan. JEL Classifications: F1, O2, P